Penguatan nilai-nilai Pancasila sebagai dasar negara dalam menghadapi tantangan modernisasi dan globalisasi - afifah, Astia nisa azizatul (Maliki Interdisciplinary Journal, 2026)
Strengthening the values ​​of Pancasila is essential, given that the majority of the public does not yet fully understand its role as a guide to life, resulting in a decline in the nation's ideological resilience in the era of globalization. This is due to outreach activities that are still one-way and fail to raise public awareness. Furthermore, practical Pancasila education is also crucial for the younger generation. Ultimately, collaboration between the community, government, and educational institutions is crucial for Pancasila to remain meaningful and maintain national identity. A presidential system of government with its checks and balances mechanism supports the implementation of Pancasila values, creating political stability, executive accountability, and optimal public participation. Based on this discussion, several suggestions were proposed. First, Pancasila education needs to be conducted holistically, dialogically, and experimentally, so that students and the public understand the values ​​contextually, historically, and philosophically rather than merely normatively.